Pengintegrasian Sumber Belajar Digital dalam Pembelajaran Biologi bagi Guru Biologi Kabupaten Brebes - Anggraito, Yustinus Ulung; R. Susanti, R. Susanti; Mustikaningtyas, Dewi; Widiatningrum, Talitha; Alimah, Siti (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
The partner in this Community Service (CS) activity is the Brebes Regency Biology Subject Teachers' Conference (MGMP). This CS activity aims to increase Biology teachers' knowledge and skills regarding digital learning resources on Biodiversity material based on the 2023 Merdeka Curriculum. The method used is discussion and practice using digital learning resources in learning, adapting the Merdeka Curriculum. CS implementation activities include pretest, conceptual strengthening, and practice using digital learning resources, post-tests, and independent assignments. The material for CS activities is using the NCBI database; viruses, vaccines, and their problems; creating a phylogenetic tree using the MEGA 11 program; SINTA as a learning resource; and integrating digital learning resources in learning. The knowledge test results showed that 73.3% of participants completed it, with an average N-gain of 0.6 (medium category). The post-test score was significantly different from the pretest score based on the T-test and as many as 70% of participants completed the task independently. From the activity results, it can be concluded that participants' knowledge of digital learning resources has increased and they are skilled at using them in learning design. Mastery of digital learning resources helps teachers face the Era of Society 5.0.